Powstanie styczniowe - Kieniewicz, Stefan (Warszawa : Krajowa Agencja Wydawnicza, 1987)
A detailed account of the failed Polish rebellion of January 1863 against the three partitioners: Austria, Prussia, and Russia.
Cover title.
Includes bibliographical references (p. 78)
Keywords: Poland -- History -- Revolution, 1863-1864.